Suberized Cell Walls of Cork from Cork Oak Differ from Other Species - Teixeira, Rita Teresa; Pereira, Helena (Microscopy and Microanalysis, 2010)
Plants have suberized cells that act as protective interfaces with the environment or between different plant tissues. A lamellar structure of alternating dark and light bands has been found upon transmission electron microscopy (TEM) observation of cork cells and considered a typical feature of the suberized secondary wall. We observed cork cells from periderms of Quercus suber, Quercus cerris, Solanum tuberosum, and Calotropis procera by TEM after uranyl acetate and lead citrate staining. A lamellated structure was observed in S. tuberosum and C. procera but not in Q. suber and Q. cerris where the suberized cell wall showed a predominantly hyaline aspect with only a dark dotted staining. Removal of suberin from Q. suber cells left a thinner secondary wall that lost the translucent aspect. We hypothesize that the species' specific chemical composition of suberin will result in different three-dimensional macromolecular development and in a different spatial location of lignin and other aromatics. A lamellated ultrastructure is therefore not a general feature of suberized cells.
Keywords: cell wall; Cork; lamellae; Quercus suber; suberin; ultrastructure